Washington State Short-Line Railroads: Case Study in Meeting 21st-Century Demands with 19th-Century Infrastructure. Issue 1 (2016) - Sage, Jeremy; Eustice, J. Bradley; Casavant, Ken; Herman, Chris
Following the Staggers Act of 1980, the Class I railroads in Washington State abandoned nearly 2, 000 mi of rail line, as similar events occurred throughout the country. This abandonment generated the opportunity for the creation of many short-line railroads on branch and light-density lines. Recognition of the degree of deferred maintenance throughout the country has become increasingly prevalent in recent years. Many short lines have not been upgraded to meet the standards and conditions required for modern freight rail load limits (286, 000 lb per car) and frequently rely on century-old rail lines. Through in-depth interviews of short-line operators and owners, this paper finds that more than 55% (740 mi) of all current short-line miles within Washington State are unable to handle 286, 000-lb railcars efficiently, putting those operators and owners at an increasing economic disadvantage. Overcoming this deficiency and bringing the state's short-line system to Class II operating status will require infrastructure investments in excess of $600 million. The annual need throughout the state exceeds the current funding capabilities of most lines through their own revenue streams and public support, even if considered over a 20-year planning horizon. To put the effects of deferred maintenance in perspective, three short-line case studies illustrate the private and public benefits of investment in the short-line railroad system to ensure that short lines remain viable operations.